Exploring Digitalization within the Tourism Supply Chain Network - Portia Pearl Siyanda Sifolo (LPPM of NAROTAMA UNIVERSITY, 2023)
Purpose: Digitalisation among SMMEs has been slow due to the constraints such as a lack of infrastructure, networks, technologies, and related skills to fast-track digital transition. These binding constraints make it harder for Small Micro and Medium Enterprises (SMMEs) in developing countries to undertake this digital transition. The purpose of this study is to explore the state of digitalisation within the Tourism Supply Chain Network (TSCN) among SMMEs in Gauteng. Design/ Methodology/ Approach: An ethnographic qualitative methodology was adopted to have a better understanding of the complexity and idiosyncrasies of digitalisation within the TSCN among the SMMEs in Gauteng where interviews were conducted from twelve participants until saturation. Findings: The results revealed that apart from the lack of digital skills (data analytics software and video editing technology) and limited understanding of knowledge management especially for the legal systems within the supply network among the selected SMMEs remains a challenge. Practical Implication: Formulating integrated business ventures and approaching big projects as consortiums not as individual small micro entities is critical for more purpose-driven tourism networks, especially for emerging businesses. SMMEs hardly work with other businesses in the area to develop sustainable networks; hence, there is a need for an effective travel and tourism data Management Company connecting both international and domestic suppliers for effective and efficient service to the businesses and the customers. Paper type: Research paper